IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI PROGRAM TCB DI SD DARUL HIKAM BANDUNG - Siti Zuliana; Rani Aulia Mawardhani; Widya Dinda Risti; Erisa Sindyana; Elya Umi Hanik (Universitas Islam Darul 'Ulum Lamongan, 2022)
This study aims to identify the role of schools in implementing character education through the Darul Hikam program, namely the Taqwa Character Building (TCB) program. This study uses a descriptive method with a qualitative approach. Data collection techniques in the form of observation, documentation and literature study. Based on the results of the study, it can be concluded that in the implementation of character education through the TCB program at SD Darul Hikam , we can see that in their daily life, SD Darul Hikam implements a motivational ceremony or apple, goes to class, reads it before learning activities begin, performs dhuha prayers, study activities, perform the obligatory prayers, eat lunch together and continue the task of studying until it is finished. In the TCB program, the teacher acts as a role model for students . The TCB program is classified into 7 characters, namely sincere, intelligent, caring, patient, trustworthy, disciplined, and sincere. These seven (7) characters are implemented gradually from month to month. By carrying out each month students can understand and practice it gradually. Because instilling character and morals takes a long time, especially for elementary school-aged children.